Die Fläche : design and lettering of the Vienna secession, 1902-1911 - Reynolds, Diane; Reynolds, Dan; Brandow-Faller, Megan; Letterform Archive (San Francisco, California) (San Francisco : Letterform Archive Books, 2023)
"Die Fläche is the first volume in Letterform Archive's facsimile series, which presents landmarks of print and design history with exacting reproductions and new essays that provide rich context and fresh insights. The brainchild of Koloman Moser, Alfred Roller, Josef Hoffmann, Bertold Löffler, and others, the leading graphic artists of the Vienna Secession and the Wiener Werkstätte--Die Fläche (German for The Surface) lays out an extraordinary group vision for design through adventurous work by these designer-professors and over a hundred of their students.^
Packed with bold ideas for posters, advertisements, book covers, woodcut prints, and much more, the result is an inexhaustibly rich sourcebook of graphic forms, modern ideas, and technical experiments, all reflecting a reorientation in design practice and teaching that would resonate around the world.This full-size facsimile of all fourteen issues of Die Fläche lets readers experience this rare gem as it was meant to be seen, while new essays and translations explore its significance.1 Die Fläche: Surface and DepthDiane Silverthorne situates Die Fläche in the exuberant cultural moment of Vienna around 1900, introducing the creative forces behind its making,^
exploring its pioneering vision for a modern2 Rudolf von Larisch: Vienna's Theorist of Artistic WritingDan Reynolds sheds light on the fascinating neglected figure responsible for the many innovations in lettering associated with the Vienna Secession and appearing throughout Die Fläche.3 Women Art Students and the Art of "Unlearning" in Die FlächeMegan Brandow-Faller reveals the contributions of the many women designers featured in the pages of Die Fläche, showing how a feminist idea of "unlearning" fueled transformative engagements with folk, East Asian, and children's art, as well as new approaches to stenciling and woodcut printing.4 Translated essays from Die Fläche, by Josef August Lux5 Selected artist biographies, an index of artists, a glossary of translated terms, and two volume walkthroughs6 Full facsimiles of Die Fläche I and Die Fläche II"--
boek
Keywords: Oostenrijk